Compressive properties of open-cell ceramic foams - 张俊彦 傅衣铭 曾晓明 (Transactions of Nonferrous Metals Society of China, 2006)
The compressive experiments of two kinds of ceramic foams were completed. The results show that the behavior of ceramic foams made by organic filling method is anisotropic. The stress-strain responses of ceramic foams made by sponge-replication show isotropy and strain rate dependence. The struts brittle breaking of net structure of this ceramic foam arises at the weakest defects of framework or at the part of framework, which causes the initiation and expanding of cracks. The compressive strength of ceramic foam is dependent on the strut size and relative density of foams.